Rooting Administrative Functions in The Light of The Holy Qur’an and The Sunnah: A Comparative Study with Modern Administrative Thought to Build an Integrated Islamic Administrative Model - Alakroot, Najla Farhat (Journal of Economic, Administrative and Legal Sciences, 2025)
This study seeks to establish the four managerial functions-planning, organizing, directing, and controlling-in light of the Qur’an and the Prophetic Sunnah, and to compare them with modern management concepts and models, with the aim of developing a comprehensive Islamic management model that balances institutional efficiency with ethical values. The study adopts a descriptive-analytical and comparative approach through examining Islamic texts in relation to managerial concepts, identifying similarities, differences, and opportunities for integration. The findings indicate that the Islamic managerial perspective is characterized by its value-based reference rooted in Sharia, integrating both material and spiritual dimensions to achieve a balance between institutional objectives and moral purposes, while maintaining adaptability to contemporary challenges. The study recommends incorporating Islamic values into modern administrative practices, designing training programs for leaders and managers that include principles of Islamic management, Shura (consultation), and leadership by example, and enhancing dual control systems (self and institutional) aligned with Sharia-based values. Furthermore, it encourages applied research to test the effectiveness of the proposed Islamic management model within contemporary organizational contexts.
Keywords: Islamic management; managerial functions; modern management thought; planning; organizing; directing; controlling; Qur’an; Prophetic Sunnah; integrated Islamic management model